Insights into the mechanism and regulation of pyruvate carboxylase by characterisation of a biotin-deficient mutant of the Bacillus thermodenitrificans enzyme - Abdussalam Adina-Zada (2018)
Pyruvate carboxylase is a biotin-dependent enzyme in which the biotin is carboxylated by a putative carboxyphosphate intermediate that is formed in a reaction between ATP and bicarbonate. The resultant carboxybiotin then transfers its carboxyl group to pyruvate to form oxaloacetate. In the Bacillus thermodenitrificans enzyme the biotin is covalently attached to K1112. A mutant form of the enzyme (K1112A) has been prepared which is not biotinylated. This mutant did not catalyse the complete reaction, but did catalyse ATP-cleavage and the carboxylation of free biotin. Oxaloacetate decarboxylation was not catalysed, even in the presence of free biotin, suggesting that only the biotin carboxylation domain of the enzyme is accessible to free biotin. This mutant allowed the study of ATP-cleavage both coupled and not coupled to biotin carboxylation. Kinetic analyses of these reactions indicate that the major effect of the enzyme activator, acetyl CoA, is to promote the carboxylation of biotin. Acetyl CoA reduces the Kms for both MgATP and biotin. In addition, pH profiles of the ATP-cleavage reaction in the presence and absence of free biotin revealed the involvement of several ionisable residues in both ATP-cleavage and biotin carboxylation. K1112A also catalyses the phosphorylation of ADP from carbamoyl phosphate. Stopped-flow studies using the fluorescent ATP analogue, formycin A-5′-triphosphate, in which nucleotide binding to the holoenzyme was compared to K1112A indicated that the presence of biotin enhanced binding. Attempts to trap the putative carboxyphosphate intermediate in K1112A using diazomethane were unsuccessful. © 2008 Elsevier Ltd. All rights reserved.